Nonimmune hydrops fetalis associated with extralobar pulmonary sequestration: Case report - (:unkn) unknown (My University, 1997)
Nonimmune hydrops fetalis is a rare congenital anomaly resulting from a variety of conditions. Extralobar pulmonary sequestration leads to hydrops and hypoplasia of the adjacent structures. A case of nonimmune hydrops fetalis associated with extralobar pulmonary sequestration and ipsilateral pulmonary hypoplasia is presented.
Keywords: Extralobar pulmonary sequestration; Hydops fetalis